A novel mouse model of Campylobacter jejuni enteropathy and diarrhea. - Natasa Giallourou; Gregory L Medlock; David T Bolick; Pedro Hqs Medeiros; Solanka E Ledwaba; Glynis L Kolling; Kenneth Tung; Patricia Guerry; Jonathan R Swann; Richard L Guerrant (PLoS Pathogens, 2018)
Campylobacter infections are among the leading bacterial causes of diarrhea and of 'environmental enteropathy' (EE) and growth failure worldwide. However, the lack of an inexpensive small animal model of enteric disease with Campylobacter has been a major limitation for understanding its pathogenesis, interventions or vaccine development. We describe a robust standard mouse model that can exhibit reproducible bloody diarrhea or growth failure, depending on the zinc or protein deficient diet and on antibiotic alteration of normal microbiota prior to infection. Zinc deficiency and the use of antibiotics create a niche for Campylobacter infection to establish by narrowing the metabolic flexibility of these mice for pathogen clearance and by promoting intestinal and systemic inflammation. Several biomarkers and intestinal pathology in this model also mimic those seen in human disease. This model provides a novel tool to test specific hypotheses regarding disease pathogenesis as well as vaccine development that is currently in progress.